Chopin, Pianos and East Asian Modernity - Samson , Jim (Chopin Review, 2023)
For music to have an identity, it seems, it must belong to someone. I will argue that in the twenty-first century Chopin no longer belongs to Europe. Can we really speak of ‘Chopin reception’ in East Asia today, given that he now belongs to these cultures too? Already in the early twentieth century, the piano emerged as a potent symbol of modernity in East Asia, and today the success of East Asian pianists in the International Chopin Competition has become a matter of the greatest national pride for relevant nations. In this paper I will ask if socio-political modernities in East Asia, and the cultural modernisms that followed them and responded to them, are distinguishable from those of ‘the West’. Which are the common factors, and which the unique, bearing in mind that modernists of both East and West cultivated and relished temporal distance (now vs then), as well as spatial distance (here vs there)? In addressing cultural encounters between East and West, I heed Jürgen Osterhammel’s caution against prematurity in the identification of dichotomous discourses. I also invoke the theoretical concept of ‘cultural lag’, a concept of some vintage, but one that can have explanatory value when we consider the counterpoints and synergies generated between science, politics and culture in both East and West. In reflecting on Chopin in East Asia, I contextualise cultural transfer in several ways. These include aesthetic responses to collective trauma, not least through the establishment of a tabula rasa, or alternatively through a mode of (depthless) imitation that celebrates what Susan Sontag called ‘sensuous surface’. They also include a surrender to mechanism, and a tendency to fetishise or iconise cultural figures. All of these are arguably symptomatic of East Asian modernisms.